From record to data. Linked data and information seeking in the OPAC. - Antonella Iacono (JLIS.it, 2013)
The application of linked data to catalogue data opens up new perspectives for OPAC development. The new relationships between bibliographic and other data will produce cataloguess that are deeply integrated with the Web, giving a decisive impact on the structure of catalog records, on access and on the functions that the catalog can play in the wider global information space. In this paper the author explores the possibility the new record deconstructed and connected with the other data on the Web is able to facilitate the creation of knowledge in the use of the catalogue. The author then analyzes the potential of application of linked data to the catalogue with regards to the capabilities for research, the new possibilities of semantic search and the ways to access bibliographic data.